Engaging Non-State Armed Groups and Gangs in Peace Process in Nepal - Thapa, Sujata (New Angle: Nepal Journal of Social Science and Public Policy, 2011)
The peace process in Nepal has been slow and fragile with many hurdles and drawbacks. Nepal is in the crossroad to peace and democracy- there is still a long road ahead for establishing a democratic country. This article traverses through the critical juncture of the country’s history by analyzing the situation of eastern Tarai in the context of an increasing number of youths joining non-state armed groups and forces. This development had led to insecurity in the region and can seriously derail the ongoing peace process in Nepal. This article is based on the in-depth interviews conducted with the armed group members, local youth and community elders. The field work spanned almost two years from early 2009 to the end of 2010. The findings show that the motivations of armed groups are as varied as their respective nature of operation. The paper provides the implication of these groups to the ongoing peace process in Nepal and offers some recommendations toward restoring peace and rebuilding normal lives and livelihoods.